LIVIU REBREANU - CREATOR DE DESTINE. SEMNIFICAŢIILE UNEI BIBLIOGRAFII - KULIKOVSKI, Lidia (BIBLIOPOLIS, 2020)
The study presents a quantitative and qualitative analysis of Rebreanu work in libraries from Moldova compared to a reference unit - County Library "George Coşbuc" in Bistrita Nasaud. The analysis was performed using the catalogue-bibliography developed by the "B.P. Hasdeu"Municipal Library and edited by Bistrita Nasaud County Library.      The author analyzes the fullness of this publication, the qualitative aspect of the collection and highlights its significance for the involved libraries and the cultural aspect emphasis on the involvement and contributions of various personalities who wrote about Liviu Rebreanu, who donated autographed books to BM, who participated in various stages in numerous cultural events of the Chisinau municipal library which, in the opinion of the author brings us closer of the great novelist.